2015
DOI: 10.15761/ifnm.1000128
|View full text |Cite
|
Sign up to set email alerts
|

Digestion characteristics and kinetic analysis of bio-molecules in a simulated human intestinal system

Abstract: We designed and assembled a simulated human intestinal system (SHIS) consisting of a stomach and a small intestine. Each reactor vessel has several ports such as the input and output of medium, a sampler of liquid phase, a pH electrode, a pH control (acid and base), and a thermometer. The SHIS was kept at body temperature (37°C) by pumping water into the space between the jacket and the inside walls. The stomach chamber was initially filled with gas fluids and then digested for 2 hr. After the stomach digestio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…The alginate concentration strongly affects capsule integrity and fluid viscosity influenced by the surface tension of the stirred CaCl 2 solution. A good alternative was achieved with alginate concentrations between 1% and 2.5% (Choi et al., ). Stable calcium alginate capsules were obtained with CaCl 2 concentrations greater than 0.05 M (Keita & Imai, ), whereas a high Ca 2+ concentration (16 g/100 mL) in the solution used for formulating capsules may decrease the viability of the probiotic (Shori, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The alginate concentration strongly affects capsule integrity and fluid viscosity influenced by the surface tension of the stirred CaCl 2 solution. A good alternative was achieved with alginate concentrations between 1% and 2.5% (Choi et al., ). Stable calcium alginate capsules were obtained with CaCl 2 concentrations greater than 0.05 M (Keita & Imai, ), whereas a high Ca 2+ concentration (16 g/100 mL) in the solution used for formulating capsules may decrease the viability of the probiotic (Shori, ).…”
Section: Resultsmentioning
confidence: 99%
“…The level of capsule degradation was confirmed by analyzing the level of total carbohydrate (Choi et al., ). During the simulated GI reactions, 10 mL fluid samples were withdrawn from the stomach and small intestine vessels at 1 and 2 hr intervals, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, we used urantide, a special antagonist of GPR14, to block GPR14 and the results indicated that GPR14 inhibition alleviated DSS-induced colitis in mice evidenced by reduced rectal bleeding and histological injury, indicating a protective role of urantide in the colitis model. Pro-inflammatory cytokines and inflammation response in the gastrointestinal tract play a vital role in the progression of IBD (10,(22)(23)(24)(25). However, the effect of UII/GPR14 signaling on DSS-induced pro-inflammatory cytokine generation is not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, NF-κB signaling was activated after DSS treatment in vivo and in vivo, while inhibition of the UII/ GPR14 signal via urantide or GPR14 siRNA transfection significantly inactivated NF-κB via reducing p65 phosphorylation. NF-κB activation requires IκBs, an inhibitory protein of NF-κB (25,26,29). The present data revealed that urantide markedly alleviated the inhibitory effect of DSS on IκBα.…”
Section: Discussionmentioning
confidence: 99%
“…Bornhoeft et al (2012) reported that dietary 0.2% TP improved lipid metabolism in rats fed an atherogenic diet via mediating serum LDL-C and HDL-C concentrations. The mechanism may be that TP can regulate fatty acid synthesis and lipolysis-related genes, including carnitine palmitoyl transferase I, acyl-CoA oxidase 1, peroxisome proliferator-activated receptor-α (PPARα), adipose triglyceride lipase, and lipoprotein lipase (LPL) (Huang et al, 2013;Choi et al, 2015).…”
Section: Discussionmentioning
confidence: 99%